2023
DOI: 10.21203/rs.3.rs-2492551/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding geriatric models of care for older adults living with HIV: A Scoping Review and Qualitative Analysis

Abstract: Background Advances in Human Immunodeficiency Virus (HIV) treatment have reduced mortality rates and consequently increased the number of individuals with HIV living into older age. Despite this, people aged 50 years and older have been left behind in recent HIV treatment and prevention campaigns, and a gold-standard model of care for this population has not yet been defined. Developing evidence-based geriatric HIV models of care can support an accessible, equitable, and sustainable HIV health care system tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(49 reference statements)
0
3
0
2
Order By: Relevance
“…SOUZA et al, 2023). Kokorelias et al (2023) destacam que o estigma associado à doença pode gerar medo em relação à revelação do diagnóstico, resultando em atrasos no início do tratamento. Além disso, o receio de sofrer discriminação por parte dos profissionais de saúde pode também, levar à hesitação ou recusa na busca por atendimento médico oportuno.…”
Section: Introductionunclassified
“…SOUZA et al, 2023). Kokorelias et al (2023) destacam que o estigma associado à doença pode gerar medo em relação à revelação do diagnóstico, resultando em atrasos no início do tratamento. Além disso, o receio de sofrer discriminação por parte dos profissionais de saúde pode também, levar à hesitação ou recusa na busca por atendimento médico oportuno.…”
Section: Introductionunclassified
“…Investigations into impactful and appropriate models of care for older persons living with HIV are limited. We conducted a systematic synthesis of existing models of geriatric HIV care to identify the key components and inform novel geriatric-HIV models of care within Canada (Kokorelias et al, 2023). Our review found that, while numerous models have been implemented with geriatricians taking on responsibilities ranging from consultation to leadership roles, no model considered the role of culturally-appropriate care.…”
Section: Introductionmentioning
confidence: 99%
“…Our review found that, while numerous models have been implemented with geriatricians taking on responsibilities ranging from consultation to leadership roles, no model considered the role of culturally-appropriate care. Moreover, none of the existing models were from Canada or delivered care in rural and remote communities (Kokorelias et al, 2023), despite people living in this setting being disproportionately impacted by HIV with increased frailty outcomes, and less treatment uptake and viral suppression (PHAC, 2020). A similar review explored the confidence of geriatricians in managing the care of older persons living with HIV and concluded their lack of comfort in dealing with intersecting identities (Jones & Barber, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOUZA et al, 2023). Kokorelias et al (2023) destacam que o estigma associado à doença pode gerar medo em relação à revelação do diagnóstico, resultando em atrasos no início do tratamento. Além disso, o receio de sofrer discriminação por parte dos profissionais de saúde pode também, levar à hesitação ou recusa na busca por atendimento médico oportuno.…”
Section: Introductionunclassified